Bolus injection of thrombolytic agents during cardiopulmonary resuscitation for massive pulmonary embolism - Böttiger, Bernd W.; Böhrer, Hubert; Bach, Alfons; Motsch, Johann; Martin, Eike (Resuscitation, 1994)
Thrombolytic therapy has proved to be efficacious in the treatment of massive and fulminant pulmonary embolism (PE), but thrombolysis has been considered as contraindicated during cardiopulmonary resuscitation (CPR). This review on the administration of thrombolytic agents in patients who have suffered massive PE necessitating CPR summarises 14 anecdotal reports and three case series involving 34 patients. The case series revealed an overall initial survival rate of 55-100% following bolus administration of thrombolytic agents. In general, bleeding complications were managed conservatively. The establishment of the diagnosis may be feasible using echocardiography or bedside angiography during CPR. However, therapeutic measures should be taken without delay; the patient's history and the clinical picture may thus be the only diagnostic criteria. Even where myocardial infarction is misinterpreted as PE during CPR, bolus injection of a thrombolytic agent can be an appropriate therapeutic option. An alternative may be mechanical catheter fragmentation of the thrombus with subsequent local thrombolysis. Surgery may be restricted to hospitals with ready access to extracorporeal circulation. We conclude that early administration of thrombolytic agents during PE necessitating CPR may help to reduce mortality. We favour the administration of urokinase (2- to 3 000 000-U bolus) or rt-PA.